2002
DOI: 10.1089/105072502760258686
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Tumor Burden and Serum Thyroglobulin Level in Patients with Papillary and Follicular Thyroid Carcinoma

Abstract: Serum thyroglobulin (Tg) is a reliable marker for detecting recurrent and persistent disease during the follow-up of patients with papillary and follicular thyroid carcinoma. The goal of this study was to assess the relationship between the serum Tg level measured after thyroid hormone withdrawal and the tumor mass in thyroid cancer patients who underwent surgery with the use of an intraoperative probe for lymph node metastases with (131)I uptake. Patients were classified into one of three groups according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 9 publications
4
80
1
1
Order By: Relevance
“…Intermediate-risk patients have microscopic invasion of tumor into the perithyroidal soft tissues at initial surgery or tumor with aggressive histology or vascular invasion (180)(181)(182). High-risk patients have macroscopic tumor invasion, incomplete tumor resection, distant metastases, or 131 I uptake outside the thyroid bed on the post-treatment scan done after thyroid remnant ablation (183,184).…”
Section: Differentiated Thyroid Cancer: Long-term Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermediate-risk patients have microscopic invasion of tumor into the perithyroidal soft tissues at initial surgery or tumor with aggressive histology or vascular invasion (180)(181)(182). High-risk patients have macroscopic tumor invasion, incomplete tumor resection, distant metastases, or 131 I uptake outside the thyroid bed on the post-treatment scan done after thyroid remnant ablation (183,184).…”
Section: Differentiated Thyroid Cancer: Long-term Managementmentioning
confidence: 99%
“…The use of recovery assays for this purpose is controversial (184,198). Serial serum antithyroglobulin antibody measurements may serve as an imprecise surrogate marker of residual normal thyroid tissue or tumor (198,199).…”
Section: What Is the Role Of Serum Thyroglobulin Assays In The Followmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Serum Tg or TgAb levels are strongly affected by the tumor volume, and the tumor burden is one of the main factors that contributes to negative 18 F-FDG PET/ CT results. 15 Many studies have shown that the possibility of obtaining positive findings on PET increases with increasing Tg levels. Schl€ uter et al 16 suggested that 18 F-FDG PET/CTpositive findings correlated positively with increasing Tg levels, and they suggested 18 F-FDG PET/CT is useful at Tg levels of 10 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, there was no significant difference of baseline serum Tg between the two groups. Some studies suggest that pre-ablation Tg is related with remnant burden [22], although serum Tg is not actively released into blood stream in proportion to cellular burden and has limitation in estimation of small remnant burden. In addition, there is no known relationship between iodine uptake and remnant burden, although similar iodine uptake intensity suggested similar iodine accumulation [23].…”
Section: Discussionmentioning
confidence: 99%